The estimation and translation uncertainties in applying NOAEL to clinical dose escalation - Chao Chen; Silvia Maria Lavezzi; David McDougall (Wiley, 2024)
Abstract The systemic exposure at the no‐observed‐adverse‐effect‐level (NOAEL) estimated from animals is an important criterion commonly applied to guard the safety of participants in clinical trials of investigational drugs. However, the discrepancy in toxicity profile between species is widely recognized. The objective of the work reported here was to assess, via simulation, the level of uncertainty in the NOAEL estimated from an animal species and the effectiveness of applying its associated exposure value to minimizing the toxicity risk to human. Simulations were conducted for dose escalation of an investigational new chemical entity with hypothetical exposure‐response models for the dose‐limiting toxicity under a variety of conditions, in terms of between‐species relative sensitivity to the toxicity and the between‐subject variability in the key parameters determining the sensitivity and pharmacokinetics. Results show a high uncertainty in the NOAEL estimation. Notably, even when the animal species and humans are assumed to have the same sensitivity, which may not be realistic, limiting clinical dose to the exposure at the NOAEL that has been identified in the animals carries a high risk of either causing toxicity or under‐dosing, hence undermining the therapeutic potential of the drug candidate. These findings highlight the importance of understanding the mechanism of the toxicity profile and its cross‐species translatability, as well as the importance of understanding the dose requirement for achieving adequate pharmacology.